2021
DOI: 10.1111/all.14964
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic pleural effusion and stroke with cutaneous vasculitis: Two cases of dupilumab‐induced hypereosinophilia

Abstract: https://www.cdc. gov/vacci nes/covid -19/info-by-produ ct/clini cal-consi derat ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 9 publications
0
10
0
3
Order By: Relevance
“…Unter einer Dupilumab-Therapie kann es zu einem deutlichen (meist transienten) Anstieg der Bluteosinophilen kommen: hier korreliert die Bluteosinophilenzahl nicht mit den Asthma-Symptomen des Patienten (Patienten können trotz hoher Bluteosinophilenzahlen ein gute Asthmakontrolle aufweisen) [127]. Die Bluteosinophilen-Vermehrung bei Biologika-naiven Patienten ist ein wichtiger prognostischer Marker für das Ansprechen auf eine Therapie mit Anti-IL-5-(R)-Biologika: je höher der Bluteosinophilenwert, desto wahrscheinlicher das Ansprechen [128].…”
Section: Leitlinieunclassified
See 1 more Smart Citation
“…Unter einer Dupilumab-Therapie kann es zu einem deutlichen (meist transienten) Anstieg der Bluteosinophilen kommen: hier korreliert die Bluteosinophilenzahl nicht mit den Asthma-Symptomen des Patienten (Patienten können trotz hoher Bluteosinophilenzahlen ein gute Asthmakontrolle aufweisen) [127]. Die Bluteosinophilen-Vermehrung bei Biologika-naiven Patienten ist ein wichtiger prognostischer Marker für das Ansprechen auf eine Therapie mit Anti-IL-5-(R)-Biologika: je höher der Bluteosinophilenwert, desto wahrscheinlicher das Ansprechen [128].…”
Section: Leitlinieunclassified
“…* Unterschiedliche Bluteosinophilen-Grenzwerte in den Zulassungsstudien von Mepolizumab, Reslizumab und Benralizumab. ** Eine Dupilumab-Therapie-Einleitung sollte aufgrund der Gefahr schwerer Hypereosinophilien bei Bluteosinophilen-Ausgangswerten > 1500/µl nur in begründeten Fällen erfolgen[127]. & Omalizumab ist für die Behandlung der chronisch spontanen Urtikaria ab einem Alter von 12 Jahren und für die Behandlung der CRSwNP ab 18 Jahren zugelassen.…”
unclassified
“…However, the ROC curve of CXCR4 was excellent, with an area of 94% under the curve, and a sensitivity of 88%. Although dupilumab‐induced transient eosinophilia seems not clinically relevant in the majority of cases, 22–25 there are case reports with dupilumab‐associated hypereosinophilic syndromes 60–62 . Therefore, CXCR4 on eosinophils might be a valuable predictive marker for stratifying patients who might develop eosinophilia and should be monitored more carefully under the treatment with dupilumab.…”
Section: Discussionmentioning
confidence: 99%
“…In our patient, we observed leukocytosis and eosinophilia. Lommatzsch et al presented a case that involved dupilumab-induced hypereosinophilia, which led to eosinophilic pleural effusion within the first six weeks after treatment initiation [ 9 ]. Another study showed that blood eosinophils transiently increased after dupilumab in patients with asthma or chronic sinusitis, but not in atopic dermatitis or eosinophilic esophagitis.…”
Section: Discussionmentioning
confidence: 99%